The Pattern of Early Childhood Character Education in Villages and Cities: A Study in Tulungagung Regency, East Java - Keppi Sukesi; Inggrida, Jedda Ayu; Nurhadi, Iwan (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2021)
The pattern of early childhood education is paramount to be attentively concerned as the instrument to immerse children's attitude and behavior. The present study was conducted in Tulungagung Regency, East Java. The study was initially started by selecting early childhood schools with village-city and public and religious-based criteria, namely 2 Early Childhood Schools (ECS) in the city area in Tulungagung and 2 in the village area. Using qualitative and quantitative methods by surveying the parents of 30 students, focus group discussions with 20 participants, and in-depth studies in schools, the study has arrived at some interpretative points. First, parenting in villages and cities showed the same pattern and was dominated by authoritative parenting patterns, meaning that the parents give choices to their children. Second, parenting showed different gender values and norms in which the daughter was treated to be more feminine than the son. Third, the different availability of the space area for playing outside the classroom between in the villages and the cities. In the city, girls had limited areas to play. Fourth, teaching materials, leadership, and group work were carried out jointly between girls and boys. The curriculum and school management have not been gender-sensitive and show no difference between village and city. Moreover, the focus of the curriculum is character education.